Modelo de implementación del reporte de sostenibilidad bajo el Global Reporting Initiative (GRI) a Premontec S.A.S. (2022)
The realization of the thesis, on the implementation model of the sustainability report under the Global reporting initiative, shows to all interest groups the importance of sustainable business development in times of the 21st century, because at present it has been possible to highlight global problems related to the impact generated by human activity and industry that generally show high levels of pollution, as well as deterioration in the environment, which drives different sectors, companies and individuals to provide solutions and contribute to compliance with the sustainable development goals. Through this project we will apply the sustainability report in the company Premontec SAS, through a descriptive-proposal type investigation that will allow us to identify the material issues of the company, determine the management of impacts, and structure the sustainability report and in turn transform Premontec into a triple impact company as an agent of change.